Green Minds: An Introspective Look at Gardening Curriculum for Science Skills in Preschoolers (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Gardening with preschool children is often limited to basic gardening activities. Digging holes, planting seeds, watering growing vegetables, and observation of plants are common activities for teachers to use when implementing gardening curriculum. While this approach to gardening is effective for science learning, there are other innovative educational gardening experiences that teachers can curate. This paper examines indoor, formal, and digital gardening curriculum which can help preschool teachers foster sound science skills for students. Research from studies on these experiences provide evidence for helping these children learn sound scientific concepts. Potential barriers to these creative curricular activities are investigated. These gardening curricular activities can help change the current landscape of helping children learn science from nature’s soil.
Keywords: early childhood; science; gardening curriculum; preschool; environmental education